Formation of CdO films from chemically deposited Cd(OH)(2) films as a precursor - Gujar, T. P.; Shinde, V. R.; Kim, Woo-Young; Jung, Kwang-Deog; Lokhande, C. D.; Joo, Oh-Shim (ELSEVIER, 2008)
Formation of cadmium hydroxide at room temperature onto glass substrates from an aqueous alkaline cadmium nitrate solution using a simple soft chemical method and its conversion to cadmium oxide (CdO) by thermal annealing treatment has been studied in this paper. The as-deposited film was given thermal annealing treatment in oxygen atmosphere at 450 degrees C for 2 h for conversion into cadmium oxide. The structural, surface morphological and optical studies were performed for as-deposited and the annealed films. The structural analyses revealed that as-deposited films consists of mixture of Cd(OH)(2) and CdO, while annealed films exhibited crystalline CdO. From surface morphological studies, conversion of clusters to grains after annealing was observed. The band gap energy was changed from 3.21 to 2.58 eV after annealing treatment. The determination of elementals on surface composition of the core-shell nanoparticles of annealed films was carried out using X-ray photoelectron spectroscopy (XPS). (C) 2007 Published by Elsevier B.V.
Keywords: ZNO THIN-FILMS; OPTICAL-PROPERTIES; LAYER ADSORPTION; BATH DEPOSITION; TRANSFORMATION